Implementasi Pendidikan Kesehatan dalam Mata Pelajaran PJOK pada Sekolah - Rizki Hazazi Ali (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the extent of the implementation of health education in PJOK subjects in elementary schools in Pontianak City. The method used in this study is a survey method. A total of 103 PJOK teachers became the sample of this study, representing each sub-district in Pontianak City. Data collection used a questionnaire instrument that measures the level of implementation of health education in PJOK subjects. The results of the study on indicators of planning, implementation, results, and learning impact are the implementation of health education in PJOK subjects in elementary schools in Pontianak City has been running well and effectively. In conclusion, health education through PJOK plays an important role in supporting the health needs of the Pontianak community, which has tropical urban characteristics, so it is relevant in helping students face everyday health challenges. Keywords: Health Education, Physical Education, Pontianak